2000
DOI: 10.1159/000026681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antidepressants on γ-Aminobutyric Acid- and N-Methyl-<i>D</i>-Aspartate-Induced Intracellular Ca<sup>2+</sup> Concentration Increases in Primary Cultured Rat Cortical Neurons

Abstract: We investigated the effects of antidepressants on the intracellular Ca2+ concentration ([Ca2+]i) increases induced by γ-aminobutyric acid (GABA) or N-methyl-D-aspartate (NMDA) in primary cultured rat cortical neurons using fluorescence imaging. Acute treatment with imipramine inhibited GABA- and NMDA-induced increases in [Ca2+]i in a concentration-dependent manner. Doses of 30 μM clomipramine, desipramine, amoxapine and maprotiline also inhibited both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Studies have reported that imipramine may also improve NMDA receptor regulation (Takebayashi et al, 2000). In fact, acute treatment with imipramine inhibits NMDA-induced increases in intracellular calcium ([Ca 2 þ ] i ) (Takebayashi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that imipramine may also improve NMDA receptor regulation (Takebayashi et al, 2000). In fact, acute treatment with imipramine inhibits NMDA-induced increases in intracellular calcium ([Ca 2 þ ] i ) (Takebayashi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This study has explored the effect of desipramine on [ as inhibition of neurotransmitters-induced [Ca 2+ ] i increases in neurons [24] and blockade of voltage-dependent Ca 2+ channels in brain cortex synaptosomes [25]. Our data are the first to show that desipramine may increase [Ca 2+ ] i in osteoblasts.…”
Section: Discussionmentioning
confidence: 86%
“…It has been previously shown that acute treatment with maprotiline inhibits [Ca 2+ ] i increases induced in neurons by c-aminobutyric acid and N-methyl-D-aspartate (Takebayashi et al 2000). In contrast, chronic treatment with maprotiline amplifies serotonin-2A receptor-induced Ca 2+ mobilization in C6 glioma cells (Muraoka et al 1998); however, the possible effect of maprotiline on basal [Ca 2+ ] i is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…At the cellular level, maprotiline was shown to modulate the electrophysiological properties of cardiac muscles (Igawa et al 1988), to inhibit c-aminobutyric acid-and N-methyl-D-aspartateinduced increases of intracellular Ca 2+ concentration ([Ca 2+ ] i ) in primary cultured rat cortical neurons (Takebayashi et al 2000), to amplify serotonin-2A (5-HT 2A ) receptor-induced Ca 2+ mobilization in C6 glioma cells (Muraoka et al 1998), to inhibit 22 Na + influx in bovine chromaffin cells (Arita et al 1987), and to block delayed rectifier potassium current in ventricular myocytes (Casis et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation